2021
DOI: 10.3390/ani11051217
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Supplementary Microbial Additives Producing Antimicrobial Substances and Digestive Enzymes on Growth Performance, Blood Metabolites, and Fecal Microflora of Weaning Pigs

Abstract: The present study investigated the effects of microbial additives producing antimicrobial and digestive-enzyme activities on the growth performance, blood metabolites, and fecal microflora of weaning pigs from 21 to 42 d of age. A total of 144 weaning pigs (1:1 ratio of gilt and boar; 21 d of age; 7.40 ± 0.53 kg of average body weight) were randomly distributed into four supplementary levels of microbial additive (0 vs. 0.5 vs. 1.0 vs. 1.5% of fresh weight) with three pens of replication, consisting of 12 wean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
0
0
0
Order By: Relevance
“…One observation with supplementary microbial additives at the 1% level was an increase in blood glucose concentrations. Thus, higher blood glucose levels might be explained by the activity of digestive enzymes from the microbes used or a response to increased energy absorption in the intestine [50,51]. Balasubramanian et al [1] and Devi and Kim [52] found that microbial additive supplementation (0.1 or 0.2 g/kg multi-species probiotic, 0.2% medium-chain fatty acids, and 0.1% probiotic) had a significant effect on pig blood glucose concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…One observation with supplementary microbial additives at the 1% level was an increase in blood glucose concentrations. Thus, higher blood glucose levels might be explained by the activity of digestive enzymes from the microbes used or a response to increased energy absorption in the intestine [50,51]. Balasubramanian et al [1] and Devi and Kim [52] found that microbial additive supplementation (0.1 or 0.2 g/kg multi-species probiotic, 0.2% medium-chain fatty acids, and 0.1% probiotic) had a significant effect on pig blood glucose concentrations.…”
Section: Discussionmentioning
confidence: 99%